Multiplex polymerase chain reaction (M-PCR) for bacterial vaginosis detection - Tien Sang Trieu; Van Khoa Tran; Ha My Nguyen; Thi Thu Ha Nguyen; Quang Tung Le; Minh Ngoc Phung; Minh Quang Diep; Huong Ly Vu (Vietnam Journal of Science, Technology and Engineering, 2019)
Bacterial vaginosis (BV) is one of the most common vaginal infections in women of reproductive age. If not treated promptly, the disease can lead to serious complications affecting the fertility and long-term health of women. Research on BV requires effort from a variety of disciplines and its treatment can only be determined by coordinated actions in research and treatment. Currently, BV diagnostic methods are often based on culture techniques and Gram staining. However, molecular biology research is developing and has proved to more advantageous for identifying key pathogens. Combining both methods, we conducted a study to develop a diagnostic procedure using multiplex polymerase chain reaction (M-PCR) for simultaneous and accurate detection of the bacterial species that cause BV, incurring minimal costs and time for testing.